The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/maco.201307106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water vapour on the oxidation behaviour of a conventional aluminide and a new thermal barrier coating system sintered from a slurry

Abstract: In this work, the effect of water vapour on a new thermal barrier coating system synthesised from a slurry containing Al microparticles was studied under isothermal regime at 1100 °C for short oxidation times (50 h). Both dry air and argon gas atmospheres were investigated with increasing water vapour contents (0, 5, 10% RH, relative humidity) and the oxidation mechanisms and growth kinetics of the oxide scales were compared to conventional aluminide coatings up to 50% RH. The phase transformations occurring i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The Raman spectra shown in Figs. 6. a. and b. let appear a doublet at 1400 cm -1 which is characteristic of the presence of α-Al 2 O 3 [31,32] but no signal was observed in the Raman domain ( Fig. 6.…”
Section: Influence Of Pressure -1 Vs 300 Bar -5000 H Of Exposurementioning
confidence: 97%
“…The Raman spectra shown in Figs. 6. a. and b. let appear a doublet at 1400 cm -1 which is characteristic of the presence of α-Al 2 O 3 [31,32] but no signal was observed in the Raman domain ( Fig. 6.…”
Section: Influence Of Pressure -1 Vs 300 Bar -5000 H Of Exposurementioning
confidence: 97%
“…Indeed, for the same coating thickness, the number of interfaces increases with decreasing the size of the particles. Therefore, and because interfaces are known to scatter heat in ceramic coatings [9][10][11], the greater the number of interfaces, the lower the thermal diffusivity. In addition, the HS microparticles whose shells are thicker than those of the DS ones will lead to higher heat conduction because the ratio of material vs. void is more significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, this thin foam did not display sufficient resistance to erosion by grit blasting because of the thin oxide shell of the alumina hollow spheres [6]. Previous studies that investigated the role of the microparticles' properties [7], the mechanisms of coating formation [8] or the influence of the annealing gases [9,10] on the formation of such coatings showed that it was possible to obtain different foam top coatings by varying the parameters of the annealing conditions or the microparticles of the slurry itself. In an attempt to thicken the shell and enhance the sintering of the hollow spheres, hence to improve the mechanical strength of the insulative foam, previous research aimed at controlling the annealing atmosphere to promote the growth of the oxide shells of the original microparticles while enabling enough Al to react with the Ni substrate to form the diffusion coating [11].…”
Section: Introductionmentioning
confidence: 99%